2014
DOI: 10.1016/j.clgc.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Metastatic Renal Cell Carcinoma and End-Stage Renal Disease Receiving Dialysis and Targeted Therapies: A Single Institution Experience

Abstract: Data are limited regarding outcomes in patients with end-stage renal disease (ESRD) and metastatic renal cell carcinoma (mRCC) receiving targeted therapy. We retrospectively identified patients with mRCC and ESRD treated at the University of Texas M.D. Anderson Cancer Center from 2002 to 2012. Fourteen patients were identified with a median number of targeted therapies (TTs) per patient of 3 (range, 1–4). Outcomes in patients with mRCC and ESRD were similar to those reported in patients with normal kidney func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
0
21
1
1
Order By: Relevance
“…One patient discontinued the treatment with everolimus due to pneumonitis. The median d uration of treatment was 1.9 months [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient discontinued the treatment with everolimus due to pneumonitis. The median d uration of treatment was 1.9 months [19].…”
Section: Discussionmentioning
confidence: 99%
“…More recently Shelly et al analyzed 14 patients with end-stage renal disease and with mRCC treated with target therapy (sunitinib, sorafenib, pazopanib, everolimus, temsirolimus and bevacizumab). The median number of target therapy per patient is 3, with a median duration of treatment of 28 months [19]. Masini et al also reported a multicentric retrospective Italian study evaluating the outcome of patients treated with sunitinib and sorafenib in this setting [20].…”
mentioning
confidence: 97%
“…Targeted drugs such as sorafenib, sunitinib, pazopanib, everolimus, temsirolimus, and axitinib have recently been developed, and this has dramatically changed the therapeutic approach and disease prognosis . Very few clinical trials include patients with renal impairment; however, some retrospective analyses have shown that molecularly targeted therapies can benefit patients with ESRD . Axitinib as a single agent has been shown to have an acceptable safety profile, and it has been observed to demonstrate anti‐tumor effects in Japanese patients with mRCC .…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, почечная недо-статочность вряд ли будет иметь клиническое значение при применении препарата. Следует отметить, что в слу-чае тяжелой почечной недостаточности (клиренс креати-нина < 30 мл/мин) применение пазопаниба не изучалось, и исследования в этом направлении представляются интересными и оправданными [9].…”
Section: фармакодинамикаunclassified